Surgical trials of using a new ruminal cannula in sheep - Hegazi, Ashraf abdel-hamid; Akraiem, Almahdi. M. (Al-Mukhtar Journal of Sciences, 2012)
Ruminal cannulation in sheep either for investigation of digestion or collection of ruminal samples this performed by many types of cannulas and techniques. we used modified cannula for sheep and a new technique for implantation through one-stage operation.used without any complication